2016
DOI: 10.1002/2014wr016476
|View full text |Cite
|
Sign up to set email alerts
|

Global sampling to assess the value of diverse observations in conditioning a real‐world groundwater flow and transport model

Abstract: The use of additional types of observational data has often been suggested to alleviate the ill-posedness inherent to parameter estimation of groundwater models and constrain model uncertainty. Disinformation in observational data caused by errors in either the observations or the chosen model structure may, however, confound the value of adding observational data in model conditioning. This paper uses the global generalized likelihood uncertainty estimation methodology to investigate the value of different ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…However, as soon as observations of Q GW in the form of spring discharge were included alongside observations of H, Q SW , and T, the information from T for hydraulic parameters became negligible—observations of T then only helped informing thermal parameters. In another equally rigorous study that systematically analyzed the data worth of observations of T alongside other observation types, Delsmann et al () quantified the value of observations of H, T, Q GW , and C for the calibration of an IFM. The worth of different observation types in calibrating an IFM was estimated using a uniform random sampling approach (generalized likelihood uncertainty estimation; Beven & Binley, ; Stedinger et al, ).…”
Section: Review Of the Use Of Unconventional Observation Typesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, as soon as observations of Q GW in the form of spring discharge were included alongside observations of H, Q SW , and T, the information from T for hydraulic parameters became negligible—observations of T then only helped informing thermal parameters. In another equally rigorous study that systematically analyzed the data worth of observations of T alongside other observation types, Delsmann et al () quantified the value of observations of H, T, Q GW , and C for the calibration of an IFM. The worth of different observation types in calibrating an IFM was estimated using a uniform random sampling approach (generalized likelihood uncertainty estimation; Beven & Binley, ; Stedinger et al, ).…”
Section: Review Of the Use Of Unconventional Observation Typesmentioning
confidence: 99%
“…The worth of different observation types in calibrating an IFM was estimated using a uniform random sampling approach (generalized likelihood uncertainty estimation; Beven & Binley, ; Stedinger et al, ). Like Bravo et al () and Kurtz et al (), Delsmann et al () carried out both synthetic and real‐world modeling experiments to investigate the data worth of different observation types for flow model calibration. Delsmann et al () showed that, overall, the inclusion of unconventional observations improved model parameters and predictions if the observations were of a sufficient quality, that is, if the observations were associated with a sufficiently small measurement error.…”
Section: Review Of the Use Of Unconventional Observation Typesmentioning
confidence: 99%
See 3 more Smart Citations